2007
DOI: 10.1074/jbc.m609701200
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Treatment of Primary Hepatocytes with Oleate Induces Insulin Resistance through p38 Mitogen-activated Protein Kinase

Abstract: Free fatty acid (FFA) is believed to be a major environmental factor linking obesity to Type II diabetes. We have recently reported that FFA can induce gluconeogenesis in hepatocytes through p38 mitogen-activated protein kinase (p38). In this study, we have investigated the role of p38 in oleate-induced hepatic insulin resistance. Our results show that a prolonged treatment of primary hepatocytes with oleate blunted insulin suppression of hepatic gluconeogenesis, and decreased insulin-induced phosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 56 publications
1
40
0
Order By: Relevance
“…In parallel to the assessment of lipid accumulation under basal culture conditions, we exposed the cells to OA, known to efficiently induce steatosis in vitro [14][15][16][17]. As expected, OA supplementation increased Oil Red O staining in all cells; however, lipid deposition remained substantially higher in STK25-overexpressing cells compared with vector control (Fig.…”
Section: Resultsmentioning
confidence: 62%
“…In parallel to the assessment of lipid accumulation under basal culture conditions, we exposed the cells to OA, known to efficiently induce steatosis in vitro [14][15][16][17]. As expected, OA supplementation increased Oil Red O staining in all cells; however, lipid deposition remained substantially higher in STK25-overexpressing cells compared with vector control (Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Serine phosphorylation of IRS-1 reduces insulin signaling through the PI 3-kinase/Akt pathway, and insulin exerts its many metabolic and pro-survival effects mainly via this pathway (3,12,13,16,28,29,31,33). We have previously demonstrated in cultured endothelial cells and hepatocytes that p38 MAPK plays a critical role in free fatty acid and tumor necrosis factor-␣-induced insulin resistance by increasing serine phosphorylation and decreasing tyrosine phosphorylation of IRS-1 (17,19). As stated above, the effect of p38 MAPK may also be related to increased cell apoptosis as it mediates the apoptotic process (36), and we (6) have recently demonstrated that p38 MAPK plays pivotal role in palmitateinduced apoptosis in cultured endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that p38 MAPK plays a central role in palmitate-induced apoptosis (6) and tumor necrosis factor-␣-induced insulin resistance (17) in endothelial cells, and in fatty acid-induced insulin resistance in hepatocytes (19). Since ischemia-reperfusion, especially reperfusion, potently activates p38 MAPK (2,22,35), we examined in the present study whether p38 MAPK modulates insulin-mediated cardioprotection against ischemia-reperfusion injury in vivo.…”
mentioning
confidence: 96%
“…Measurement of Glucose Production in Primary Hepatocytes-The glucose production from primary hepatocytes was measured as previously described (22,23). Briefly, cells were treated with EGCG for 3 h at concentrations as noted in the serum-free Williams' E medium.…”
Section: Methodsmentioning
confidence: 99%